Local risk preference and corporate policies: evidence from M&A. Issue 45 (26th September 2021) - Chen, Jeffrey (Jun); Huseynov, Fariz; Li, Bochen; Zhang, Wei
ABSTRACT: This article examines whether and how the firms' mergers and acquisitions (M&A) policies are influenced by the risk preference of local community where the firms' headquarters are located. By utilizing the different preferences towards risk-taking from the county-level religiosity-based measure, we document a significantly positive relation between the local risk preference and the likelihood of firms' M&A. Firms whose headquarters are located in the counties with a higher degree of risk tolerance are more likely to engage in takeovers or acquire riskier targets. Local risk preference also results in wealth transfer during M&A that reduces acquirers' equity value. When interacting with firm CEOs' career concern and financial compensation, we find that managerial risk-taking incentive can be significantly affected by the local risk preference, suggesting an important economic interplay between the social norms and financial decision-making.